2021
DOI: 10.1371/journal.pone.0247932
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the SDQ and longitudinal associations from pre-school to pre-teen in New Zealand

Abstract: Objective The objective of this study was to assess the validity of the Strengths and Difficulties Questionnaire in a cohort of New Zealand children followed from birth to the age of eleven. The study also aimed to assess the stability of the child data in relation to behavioural outcomes during this period. Methods Children in the Auckland Birthweight Collaborative Study were assessed at approximately 3½, 7 and 11 years of age. At all time-points parents completed the parent version of the Strengths and Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A strength of this study was the unbiased, biological measure of fetal acetaminophen exposure. All but 1 of the prior studies of the association between prenatal acetaminophen exposure and child ADHD [43][44][45][46][47][48][49] have relied on questionnaires requiring mothers to recall drug use at intervals greater than 3 months. Difficulty recalling drug use during pregnancy may result in nondifferential misclassification bias toward the null.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A strength of this study was the unbiased, biological measure of fetal acetaminophen exposure. All but 1 of the prior studies of the association between prenatal acetaminophen exposure and child ADHD [43][44][45][46][47][48][49] have relied on questionnaires requiring mothers to recall drug use at intervals greater than 3 months. Difficulty recalling drug use during pregnancy may result in nondifferential misclassification bias toward the null.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Given the uncertainty in evidence of the association between exposure to fluoridated water and child development, any research on such an association should target primary outcomes of child development that are sensitive to even small chemical injury and use instruments that can reliably measure those outcomes. The 2 instruments used in this study (SDQ and BRIEF) have shown high reliability in measuring those aspects (Nyongesa et al 2019; Thompson et al 2021). Hence, the study contributes to addressing the call to investigate the potential neurotoxic effect of fluoride (Bellinger 2019).…”
Section: Discussionmentioning
confidence: 91%
“…The SDQ is a 25-question tool which has been used to evaluate mental health status during the past 6 months of young children and adolescents aged 4–16 years 27–29. Each question is scored on a 3-point Likert scale 30. The SDQ consists of five subscales (emotion, conduct, hyperactivity, peer problems and prosocial) 30.…”
Section: Methodsmentioning
confidence: 99%
“…Each question is scored on a 3-point Likert scale 30. The SDQ consists of five subscales (emotion, conduct, hyperactivity, peer problems and prosocial) 30. The SDQ’s total difficulty scores are sum of the first four subscales with the total score of 40 (10 on each scale), where larger scores correspond to more social, emotional and behavioural difficulties 29.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation